Growth and structural characterization of BiSbTe3-ySey single crystals. (2020) - Anoop, M.D.; Yadav, Nisha; Yadav, Jyoti; Singh, Rini; Jain, Ankur; Ichikawa, T.; Kumar, Manoj
Abstract: Bi2 Te3, Sb2 Te3, and their intermixtures are classical topological insulators with relatively simple electronic band structure. These materials are well known for their near room temperature thermoelectric effect too. The tuning of the Fermi level is considered relatively easy in these materials to achieve bulk insulating character. This study aims at the preparation of BiSbTe3 with isovalent selenium substitution at tellurium site to form BiSbTe3-y Sey (0 ⩽ y ⩽ 2.5) solid solutions. Single crystals of BiSbTe3-y Sey (BSTS) were synthesized using the modified Bridgman technique. X-ray diffraction studies and morphological analysis confirmed the formation of high-quality single crystals with a rhombohedral crystal structure in the R3m phase. The lattice parameters were found to decrease monotonically with an increase in the selenium concentration. The lattice volume for the composition BiSbTe3 was 497.94 Å 3, which decreased to 432.90 Å 3 for the last composition BiSbTe0.5 Se2.5 . Energy Dispersive X-ray Spectroscopy confirmed the homogeneous distribution of the elements in the sample and its chemical composition.